The Effect Of Profitability And Corporate Social Responsibility On The Value Of Companies In State-Owned Banks Listed On The Idx - Liniarti, Sri; Nasution, Rizky Surya Andhayani; Humaira, Rafiqah; Putra, Yunanda Eka; Lubis, Farida Khairani; Gustarina, Elina Rahmawati (Cattleya Darmaya Fortuna, 2025)
This study aims to obtain empirical evidence on: (1) The Effect of Profitability Driven by ROE and NPM on Company Value (2) The Effect of Corporate Social Responsibility on Company Value. The study population is 6 state-owned banking companies listed on the Indonesia Stock Exchange in 2021-2022. The sampling technique is a saturated sample. The sample of this study is 6 companies. Data analysis with multiple regression. The results of this study conclude that: (1) ROE has a significant positive effect on the value of the company with a significance level of 0.031< 0.05 and H1 is accepted. (2) NPM did not have a significant effect on the company's value with a significance level of 0.955< 0.05 and H2 was rejected. (3) CSR did not have a significant effect on the company's value with a significance level of 0.390 < 0.05 and H3 was rejected. In this study, it is recommended: (1) Researchers use a more international standard openness index measurement, such as the Global Reporting Initiative (GRI) (2) Expand the sample by using all companies listed on the IDX, (3) The next researcher to be able to extend the research period with a larger and more diverse sample number and use a more standardized corporate social responsibility disclosure index measurement internationallyanalyze the influence of corporate social responsibility (CSR) financial performance on company value. The object of the study is all state-owned banking companies totaling 6 banks from 2018 to 2019. The independent variables are company performance (return on equity, Net Profit Margin), and Corporate Cocial Responsibility, while the dependent variable is the company's value (Tobin's Q). The data analysis used was multiple linear regression analysis. The results of this study show that ROE has a significant influence on company value, while NPM, and CSR do not have a significant influence on company value.